History, Science and Nature: boundless frontiers... - Salgueiro, Ângela; Nunes, Maria de Fátima; Albuquerque, Sara; Dias, José Pedro Sousa (Fronteira: Journal of Social, Technological and Environmental Science, 2018)
History, Science and Nature: boundless frontiers...